Volcanic-glacial interactions: GIS applications to the assessment of lahar hazards (case study of Kamchatka) - Ya. D. Muraviev; E. S. Klimenko (Лëд и снег, 2015)
On the Kamchatka peninsula, lahars or volcanogenic mudflows arise as a result of intensive snow melting caused by incandescent material ejected by volcanoes onto the surface. Such flows carrying volcanic ash and cinders together with lava fragments and blocks move with a speed up to 70 km/h that can result in significant destructions and even human victims. Formation of such water flows is possible during the whole year.Large-scale GIS «Hazards of lahars (volcanogenic mudflows)» has been developed for some volcano group as well as for individual volcanoes on the peninsula in framework of the GIS «Volcanic hazard of the Kuril-Kamchatka island arc». Main components of this database are the following: physic-geographical information on region of active volcanism and adjacent areas, on human settlements; data on the mudflow activity; data on distribution of the snow and ice reserves. This database is aimed at mapping of surrounding territories and estimating a hazard of lahars.For illustration the paper presents a map of the lahar hazards, results of calculations of the distances of ejects and maximal area of ejected material spreading in dependence on a character and power of an eruption. In future we plan to perform operational calculations of maximal possible volumes of such flows and areas of their spreading. The calculations will be made on the basis of the GIS «Volcanic hazard of the Kuril-Kamchatka island arc».A volume of hard material carried by lahars onto slopes and down to foot of the Kluchevskaya volcanic massif is estimated on the basis of data on the snow and ice reserves on volcano slopes. On the average for many years, the snow accumulation in zones of the mudflow formations their volume often reaches 15–17 millions of cubic meters. Depending on the snowfall activity in different years this value may vary within 50% relative to the norm. Further on, calculations of maximal possible volume of such flows will be performed in a real time regime with regard for a character of power of a volcano eruption and reserves of snow and ice in the mudflow-forming basins. The main objective of this work is an effort to reduce a risk of a mudflow formation and to prevent possible damages.